Unusual course of meningococcal infection with lethal outcome (brief communication) - V. A. Zinserling; Yu. V. Sukhanova; D. A. Gusev (Журнал инфектологии, 2023)
We present a brief description of lethal case of meningococcal infection in 41 y old women, diagnosed by detection of Neisseria meningitidis in blood and results of histobacterioscopic study with the absence of rash and prominent mononuclear (non purulent) infiltration of soft meninges.